SISTEM INFORMASI PENJUALAN BARANG BARU - BEKAS BERBASIS WEBSITE DI TOKO BABEKU MENGGUNAKAN ASP.NET (Information Technology and Telematics, 2013)
Babeku Shop is a trading company which is engaged in the sale of new goods - the former providing  some sorts of stuff. Website sales made online at Shop Babeku is a step to overcome the problems that exist in Babeku Store. To identify how information systems problems selling new goodsformer running Babeku shop based on website, how to design information systems sales and purchases in the store Babeku based  on the website. Software which is used to design and design a Web-Based on  Information System Sales At Stores Babeku is ASP.NET  programming language, text editor Microsoft Visual Studio 2010. The main factor of building the online sales is  in order to help companies increase sales, all this process is computerized so as to minimize paperwork and minimize the occurrence of errors and it can also facilitate in making the report so as to improve the quality of employees and improve service quality  Keywords: Information Systems, Sales